Assess the knowledge regarding thyroid disorders among patients attending medical OPD - Rana, Sonali; Sati, Rahul; Thapa, Tabita; Rana, Priyanka; Joshi, Manisha; Praveen, Shama; Pundir, Namrata; Kumar, Chandan (International Journal Of Community Medicine And Public Health, 2024)
Background: The thyroid gland is an endocrine gland consisting of two lobes connected by an isthmus, in the neck. It is found in front of the neck below the Adams apple. Thyroid gland though a small structure on the anterior aspect of neck has many important functions to perform, failing in its duty might lead to serious consequences. Methods: A non-experimental descriptive research design was conducted to assess knowledge regarding thyroid disorders among patients attending medical OPD in a selected hospital of Dehradun at Uttarakhand. A total of 100 samples were selected through purposive sampling technique. A structured knowledge questionnaire was administered through interview technique to assess the knowledge. Results: The study showed that the mean knowledge score of patients regarding thyroid disorders was 14.04±3.755. The mean percentage was 14.04. There was significant association between social habits, suffered or suffering from thyroid disorders, family history of thyroid disorders, medical history of any medicine intake and previous knowledge regarding thyroid disorders with knowledge score. Conclusions: From the findings of the study, it was conducted that Out of 100 participants 42% had good knowledge and 7% had poor knowledge, 38% had average knowledge and 13% had very good knowledge about thyroid disorders. There is a need for educational programs to create awareness and improve knowledge regarding thyroid disorders.